Retraction notice to “The impact of basin horizontal ecological compensation policies on carbon emissions: A case study of the Yangtze river economic Belt” [Heliyon 10 (2024) e28858] - Kuiyuan Jia; Ruhua Yuan (Heliyon)
This article has been retracted: please see Elsevier policy on article withdrawal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal).The authors have re-examined the article and performed additional experimental verification and, in that process, discovered that their original conclusions were oversimplified. The relationship between the studied variables is more complex and interactive that concluded in the study. As such, the interpretation, and applications of the results of the study might be affected. As such the authors have requested to retract the study and the Editor has agreed with that request.